Проблеми формування нової архітектури глобальної та регіональної безпеки України - Антонов, В.О. (Держава і право, 2010)
Досліджуються аспекти, які безпосередньо загрожують безпеці України. Основним підґрунтям, на якому можуть бути вирішені ці питання, є правове поле. Исследуются аспекти, которые непосредственно угрожают безопасности Украины. Основной площадкой, на которой могут быть решены эти вопросы, является правовое поле. We proceed from the point that problems related directly to the Ukrainian state are very important to us, would like to touch briefly on those aspects that threaten the security of Ukraine directly. Among these unsolved problems that dominate now, firstly, remain unsettled local conflicts and their possible spreading. The main ground which these problems can be solved on is the legal framework. It is necessary to find those legal mechanisms that would adjust firstly these problems. And that is where the cooperation question appears.